Optimization of green tea extract, rosemary extract, and rice bran in multifunctional bread: A concept for reduction of acrylamide and phytic acid - Mandana Tayefe; Leili Fadayi Eshkiki; Zahra Rahbar Dalir; Azin Nasrollahzadeh Masoule (Heliyon)
This research aimed to produce a multifunctional bread by adding hydrothermally processed rice bran (RB), green tea extract (GTE), and rosemary extract (RE). In the first step, hydrothermal processing was used to reduce the amount of phytic acid in RB, which decreased by 55 %. Based on the acrylamide amount, texture profile analysis, and color parameters, 3 % RB was selected as the optimum concentration in the bread formulation. The acrylamide amount in the RB-fortified bread showed a significant (p < 0.05) reduction trend with the addition of GTE and RE. So the lowest amount of acrylamide concentration was reported in the sample containing 1.5 % GTE (17.18 ppb). The addition of GTE and RE significantly (p < 0.05) decreased the hardness value of bread samples. However, the cohesiveness, springiness, and adhesiveness parameters of bread samples were significantly (p < 0.05) increased by the addition of GTE and RE. In addition, the fortified breads with 0.1 % RE and 1.5 % GTE exhibited the lowest and highest ΔE values, respectively. The addition of GTE and RE caused no adverse effect on the sensory properties of the RB-fortified bread. In conclusion, the combination of RB, GTE, and/or RE is an effective strategy for providing health benefits as well as reducing acrylamide formation in this food.